Pengaruh Penambahan Dispersant Dan Waktu Pengadukan Pada Pembuatan Scaffold Hidroksiapatit Menggunakan Sabut Gambas Sebagai Template - Heni ' Ismawati; Ahmad ' Fadli; Fajril ' Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hidroxyapatite (HA) scaffold has been widely applied in the biomedical field especially for bone implants. The purpose of this research is to determine the Influence of dispersant addition and stirring time on HA scaffold which formed using gambas sponges as template. HA slurry was made by mixing 10 grams of HA, 12 grams of aquadest, 0.2; 0.25; 0.3 grams of Darvan 821A and 1 gram of sago. Slurry was impregnated into gambas sponges. Sample then dried at 110oC for 3 hours. The green bodies was burned at 600oC for 1 hour and followed by sintering at 1250oC for 1 hour. The results showed that addition of dispersant and increasing of stirring time lead to smaller porosity and shrinkage. In addition 0,2; 0,25; and 0,3 grams dispersant, the resulting porosity in the range of 63.85-70.78%; 58.74-70.35%; and 53.42-69.66%. Shrinkage 39.43-53.71%; 27.75-50.68%; and 13.61-41.25%. Compressive strength 0.61-1.05 MPa; 2.88-3.81MPa; and 0.52-2.96 MPa. The macroporous and microporous average pore sized were 50 μm dan 5 μm.Keywords: bone implant; dispersant; gambas; hidroxyapatite; scaffold